IMPLEMENTATION LEAN PRODUCTION AND ITS IMPACT ON LOGISTICS SYSTEM IN MANUFACTURING ORANIZATION – CASE STUDY (Perner's Contacts, 2014)
Authors in the paper present a case study to show benefits of lean production in manufacturing organizations. These benefits specifically include shorter production durations due to reduced work-in-process buffers, optimized utilization of workplaces and improved overall equipment effectiveness. Other typical lean production benefits in manufacturing organizations are reduction of work-inprocess inventory, improvement of products’ quality, introduction of ergonomic solutions at workplaces, possibility to produce more product types in one production line, introduction of continuous improvement process and significant reduction of production duration which in turn bring substantial reduction of working capital.
Keywords: Value Stream Mapping; Lean Production; One Piece Flow